Consider the differential equation
The characteristic equation is
So, the complimentary solution of the differential equation is
Let "y_1(t)=e^{-t}, y_2(t)=te^{-t}"
The Wronskian of these two functions is
"w(y_1(t), y_2(t))=\\begin{pmatrix}\ne^{-t}& te^{-t} \\\\\n-e^{-t} & e^{-t}-te^{-t} \\\\\n\\end{pmatrix}\\\\\n\\implies (e^{-2t}-te^{-2t})-(-te^{-2t})\\\\\n\\implies e^{-2t}"
And compare the given equation with "y''+p(t)y^t+q(t)y=g(t)" then "p(t)=2,\\ q(t)=1, \\ g(t)=e^t\\ ln\\ t"
Now the particular solution is "yp(t)=y_1u_1+y_2u_2" where
"u_1=-\\intop\\frac{y_2(t)g(t)}{w(y_1(t),y_2(t))}\\delta t,\\ u_2=\\intop\\frac{y_1(t)g(t)}{w(y_1(t),y_2(t))}\\delta t,\\\\ \nu_1=-\\intop\\frac{(te^{-t})(e^{-t}ln\\ t)}{e^{-2t}}\\delta t,\\ u_2=\\intop\\frac{(e^{-t})(e^{-t}ln\\ t)}{e^{-2t}}\\delta t,\\\\ \nu_1=-\\intop(t\\ ln\\ t)\\delta t,\\ u_2=\\intop(ln\\ t)\\delta t\\\\\nu_1=-\\frac{t^2}{4}(2\\ ln\\ t-1),\\ u_2=t(ln\\ t-1)"
Substitute "u_1, u_2" in the particular solution "yp(t)=y_1u_1+y_2u_2"
Then is
"yp(t)=(e^{-t})(-\\frac{t^2}{4}(2\\ ln\\ t-1))+(te^{-t})(t(ln\\ t-1))\\\\\n\\implies (-\\frac{t^2}{4}(2\\ ln\\ t-1))+(ln\\ t-1)t^2e^{-t})\\\\\n\\implies (-\\frac{ln\\ t}{2}+\\frac14+ln\\ t-1)t^2e^{-t}\\\\\n\\implies (\\frac{ln\\ t}{2}-\\frac34)t^2e^{-t}\\\\"
Now, the general solution is
"y(t)=y_p(t)+y_c(t)"
"\\therefore" The required solution is "y(t)=c_1e^{-t}+c_2te^{-t}+(\\frac{ln\\ t}{2}-\\frac34)t^2e^{-t}"
Comments
Leave a comment